2014
DOI: 10.1016/j.adolescence.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of emotion regulation difficulties related to anxiety in early adolescence

Abstract: Etiological models identify difficulties in emotion regulation as potential contributors to the development and maintenance of anxiety. To date, studies with adolescents have not tested whether different types of anxiety symptoms are related to different emotion regulation difficulties. The current study aimed to examine specificity of associations between emotion regulation difficulties and symptoms of social and generalized anxiety in early adolescence. Ninety adolescents (ages 11–14 years) completed measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
(75 reference statements)
3
25
0
2
Order By: Relevance
“…Acceptance—treated frequently as the opposite of experiential avoidance (98) or as a component of mindfulness (99, 100)—has been proved to be positively associated with psychological health in both adult (101) and adolescent samples (102, 103). However, in the present study, there was no relationship between this strategy and online problem gaming.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance—treated frequently as the opposite of experiential avoidance (98) or as a component of mindfulness (99, 100)—has been proved to be positively associated with psychological health in both adult (101) and adolescent samples (102, 103). However, in the present study, there was no relationship between this strategy and online problem gaming.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has sought to investigate patterns of disrupted emotion regulation specific to individual anxiety disorders. One study suggested greater deficits in emotional clarity and non-acceptance of emotions in social anxiety disorder compared to generalized anxiety disorder (using the DERS [38]). However, another found no differences between groups of adolescents with different anxiety disorder diagnoses (using the FEEL-KJ [37]).…”
Section: Relationships Between Emotion Regulation Abilities and Symentioning
confidence: 99%
“…ER strategies have been researched mainly in adults, although recent studies have shown their relevance in childhood and adolescence (Betts, Gullone, & Allen, 2009;Gullone, Hughes, King, & Tonge, 2010;Gullone & Taffe, 2012;Larsen et al, 2013), and they have been related to psychological disorders in this population, such as anxiety, depression (i.e., Garber, Braafladt, & Weiss, 1995;Mathews, Kerns, & Ciesla, 2014;Silk, Steinberg, & Morris, 2003;Southam-Gerow & Kendall, 2002;Suveg & Zeman, 2004), aggressiveness (i.e., Bohnert, Crnic, & Lim, 2003;Dearing, Relyea, & Simons, 2002;Muñoz, Kimonis, Frick, & Aucoin, 2013;Sullivan, Helms, Kliewer, & Goodman, 2010) or eating disorders (i.e., Sim & Zeman, 2005, 2006, among others.…”
Section: Introductionmentioning
confidence: 98%